Editorial 28 - López Uribe, Cristina (Bitacora Arquitectura, 2016)
Something happens at night that completely changes our perception of things. The transparency of modern architecture, in this world of electricity loses its characteristics to acquire the opposite: it becomes bright. What is reflective becomes transparent. A building with many volumetric details becomes flat. Tall buildings escape beyond our sight in the shadows. The streets are illuminated and the pavements and textures become clearer to our sight. When history has studied night and darkness it has generally done so from the point of view of lighting, and from the progressive achievement of illuminating cities -as an indicator of social progress. Few have been those who have made history from the point of view of darkness, and written about the many ways in which men and women have faced the night. About their relationship with an event of an actual cosmological significance. Night and darkness have –naturally– been associated by men with feelings of a negative connotation, as insecurity or fear, and with the greatest of them all: the fear of the unknown. Anything could happen at night, it is the territory where all the monsters and terrors of our ancestors live, and where wizards and witches make their appearance to protect us against entities that are immaterial –because we cannot see them.